Factors that influence the performance of nurses at the Pidie Community Health Center, Pidie Regency - Ismuntania; Kartika; Mualim, Azhar; Mufida, Nurlela; Iklima (International Journal on ObGyn and Health Sciences, 2023)
Factors that influence the performance of nurses in community health centers (work performance) are the quality and quantity of work results achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. The aim of the research is to determine the description of the factors that influence the performance of nurses at the Pidie Community Health Center, Pidie Regency. This research is descriptive in nature using a cross sectional method. The population in this study was 61 people using cluster sampling techniques. Based on the results of research conducted on September 2023, the majority of nurses performed well, namely 32 respondents (52.5%). The majority of awards were unsatisfactory, namely 33 respondents (54.0%). The majority of social interactions were good, namely 55 respondents (90.2%). The majority of job satisfaction was less than satisfied, namely 36 respondents (59.0%). The employment status of the majority was NON PNS, namely 39 respondents (64.0%). It is hoped that health workers, especially nurses, can improve their performance so that excellent nursing services can be achieved and can improve health status.